Single-Cell RNA Sequencing Efficiently Predicts Transcription Factor Targets in Plants - Xie, Yunjie; Jiang, Shenfei; Li, Lele; Yu, Xiangzhen; Wang, Yupeng; Luo, Cuiqin; Cai, Qiuhua; He, Wei; Xie, Hongguang; Zheng, Yanmei; Xie, Huaan; Zhang, Jianfu (Frontiers in Plant Science, 2020)
Discovering transcription factor (TF) targets is necessary for the study of regulatory pathways, but it is hampered in plants by the lack of highly efficient predictive technology. This study is the first to establish a simple system for predicting TF targets in rice (Oryza sativa) leaf cells based on 10 × Genomics’ single-cell RNA sequencing method. We effectively utilized the transient expression system to create the differential expression of a TF (OsNAC78) in each cell and sequenced all single cell transcriptomes. In total, 35 candidate targets having strong correlations with OsNAC78 expression were captured using expression profiles. Likewise, 78 potential differentially expressed genes were identified between clusters having the lowest and highest expression levels of OsNAC78. A gene overlapping analysis identified 19 genes as final candidate targets, and various assays indicated that Os01g0934800 and Os01g0949900 were OsNAC78 targets. Additionally, the cell profiles showed extremely similar expression trajectories between OsNAC78 and the two targets. The data presented here provide a high-resolution insight into predicting TF targets and offer a new application for single-cell RNA sequencing in plants.